Model of Family Conflict Management from the Dual Roles of Papuan Women - Fitrine Christiane Abidjulu; Avelinus Lefaan; Agustina Ivonne Poli; Usman Pakasi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the conflict and dual roles of Papuan women, the sources of conflict, as well as the conflict management models used by Papuan women in carrying out their roles. This research was conducted using descriptive qualitative methods and a case study approach. This data source consists of primary data, namely data obtained from informants directly and secondary data, namely data obtained from recorded reference sources. Analysis of data obtained from the field is then presented descriptively including data reduction, data organization and interpretation. The research results show that the dual role conflict experienced by women who play multiple roles can cause obstacles in work, making it difficult to achieve success in the fields of work, family and interpersonal relationships with their husbands. Then, family support for working women is predominantly emotional (familiarity and acceptance) and informational (partner sharing) in the implementation of household affairs and child care, while instrumental support (providing assistance) is still less dominantly provided by the family so that women are the ones who work does not feel satisfaction at work and causes feelings of guilt towards his family. The model for managing family conflict among Papuan women who work in Jayapura City is used by elaborating three models, namely the coping model, strategies for combining work and family and strategies for managing dual work/family identities